Extracorporeal shock wave therapy versus dexamethasone iontophoresis as a treatment for symptomatic knee osteoarthritis - Shimaa Taha Abu El Kasem; Sahar Ahmed Abdalbary; Mohamed I. Mabrouk; Engy Badreldin S. Moustafaa; Asmaa Abonour; Rania R. Mohamed (Human Movement)
Purpose The goal of this pilot study was to compare and evaluate the efficacy of extracorporeal shock wave therapy (ESWT) and dexamethasone sodium phosphate (DEX-P) iontophoresis in patients who have unilateral symptomatic knee OA (KOA).